2017
DOI: 10.5194/acp-17-3445-2017
|View full text |Cite
|
Sign up to set email alerts
|

An Atlantic streamer in stratospheric ozone observations and SD-WACCM simulation data

Abstract: Abstract. Observation and simulation of individual ozone streamers are important for the description and understanding of non-linear transport processes in the middle atmosphere. A sudden increase in mid-stratospheric ozone occurred above central Europe on 4 December 2015. The GROund-based Millimeter-wave Ozone Spectrometer (GROMOS) and the Stratospheric Ozone MOnitoring RAdiometer (SOMORA) in Switzerland measured an ozone enhancement of about 30 % at 34 km altitude (8.3 hPa) from 1 to 4 December. A similar oz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The nudging is performed at every time step with a strength of 10 % and up to an altitude of 60 km. Hoffmann et al (2012) have shown that the nudging, although only 10 % and up to 60 km altitude, yields realistic variations of carbon monoxide (CO) in the higher mesosphere.…”
Section: Sd-waccmmentioning
confidence: 99%
“…The nudging is performed at every time step with a strength of 10 % and up to an altitude of 60 km. Hoffmann et al (2012) have shown that the nudging, although only 10 % and up to 60 km altitude, yields realistic variations of carbon monoxide (CO) in the higher mesosphere.…”
Section: Sd-waccmmentioning
confidence: 99%
“…Streamers are large-scale tongue-like structures of meridionally deflected air masses (Hocke et al, 2017;Krüger et al, 2005;Offermann et al, 1999); they are linked to enhanced or breaking planetary waves (PWs). PWs are associated with the formation of pressure systems and influence the position of the tropospheric jet.…”
Section: Introductionmentioning
confidence: 99%